Preparação de eletrodos com novos materiais à base de carbono para aplicação em eletroanalítica - Deroco, Patrícia Batista (Universidade Federal de São Carlos, 2019)
In this work, electrochemical sensors were developed using two different types of carbon material: carbon black (CB) and reticulated vitreous carbon (3D-RVC) for electrochemical studies and analytical applications. First, CB was used as the only modifier nanomaterial, being the CB nanoparticles immobilized from a dispersion in dimethylformamide, on the surface of a glassy carbon electrode. This electrode was used for quantification of mesotrione herbicide in natural waters and sugar cane sample. The obtained analytical curve showed linearity from 0.040 to 7.2 µmol L−1 with detection limit of 0.026 µmol L−1. Next, it was constructed an electrode by the electrodeposition of nanoparticles of nickel oxide/hydroxide on a film of CB and dihexadecylphosphate. This new sensor was applied in the simultaneous quantification of paracetamol and codeine in commercial pharmaceutical samples and biological samples. Linear analytical curves in the ranges from 3.0 to 47.8 µmol L−1 and 0.83 to 38.3 µmol L−1 and detection limits of 0.12 µmol L−1 and 0.48 µmol L−1 were obtained for acetaminophen and codeine, respectively. In another work, the CB was used as support for the synthesis of nanoparticles of the core-shell type of Au and Pd. This combination of nanomaterials was used for the preparation of a film on the surface of the glassy carbon electrode. This sensor was used to quantify hydrazine in water samples. The linear range obtained was 2.50 and 88.0 µmol L−1, with a detection limit of 1.77 µmol L−1. Subsequently, the evaluation of the electrochemical performance of 3D−RVC modified with gold nanoparticles (AuNPs) was the main objective of this work. The 3D−RVC was modified by two different strategies of incorporation, electrodeposition and chemical adsorption of a previously prepared nanoparticle colloidal solution. The best results in terms of analytical signal, linear range and detection limit for the probes [Fe(CN)6]3− and [Ru(NH3)6]3+, and organic molecules: paracetamol, uric acid, hydroquinone and tryptophan were obtained using the electrode modified with the AuNPs electrodeposited. So, this electrode was used for the development of a method for the determination of ferulic acid in cosmetic samples and pharmaceutical formulations, being the linear analytical curve in the concentration range from 0.07 to 2.2 µmol L−1, with detection limit of 9.0 nmol L−1. The selectivity, precision and accuracy of the all proposed methods were evaluated by possible interferences studies, intra- and inter-day repeatability measurements and comparison with UV-Vis spectroscopy or HPLC with UV-Vis detection, respectively.
Preparation of electrodes with new carbon-based materials for application in electroanalytical chemistry
Keywords: Eletroanálises; Nanopartículas metálicas; Eletrodos modificados; Carbon black; Carbono vítreo reticulado; Métodos analíticos; Electroanalysis; Metal nanoparticles; Modified electrodes; Carbon black; Cross linked glassy carbon; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA